(untitled) (Bangladesh Journal of Physics, 2020)
During the last decades, ZnO has emerged as the most promising material in optoelectronic and optical applications in the visible region as well as in the infrared and UV region. It is because of the broad direct band gap of 3.37 eV at ambient temperature and high exciton binding energy of 60 meV allowing it to utilize the ultraviolet region. In this investigation, the optical characteristics of ZnO thin film of various thicknesses (300 nm, 600 nm, 900 nm) deposited on Quartz, Fused silica and Sapphire have been studied as a function of wavelength and photon energy. To obtain this, the equations for thin film have been derived, simulated and visualized by Matlab coding language. It is observed that with the increase in the photon energy, the refractive index and extinction coefficient show an increasing tendency. The results represent that among three substrates Fused silica has the lowest refractive index, reflectance and absorbance. In the visible region, the transmission spectra show that the average transmittance of all films is 85%-95%, which is superior for solar continuums. The performance of Fused silica as transparent conducting material is better than other substrates. The present investigation might provide an environment friendly and low cost material for optoelectronic and solar cell devices. Bangladesh Journal of Physics, 27(1), 59-68, June 2020